2019
DOI: 10.1103/physrevlett.123.137202
|View full text |Cite
|
Sign up to set email alerts
|

Spin Chain Network Construction of Chiral Spin Liquids

Abstract: We show that a honeycomb lattice of Heisenberg spin-1/2 chains with three-spin junction interactions allows for controlled analytical studies of chiral spin liquids (CSLs). Tuning these interactions to a chiral fixed point, we find a Kalmeyer-Laughlin CSL phase which here is connected to the critical point of a boundary conformal field theory. Our construction directly yields a quantized spin Hall conductance and localized spinons with semionic statistics as elementary excitations. We also outline the phase di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
(96 reference statements)
1
17
0
Order By: Relevance
“…Chiral spin liquids (CSLs) [11][12][13] have been extensively studied since Kalmeyer and Laughlin proposed a spin wave function analogous to fractional quantum Hall states [14,15]. The Kalmeyer-Laughlin CSL can be stabilized as the ground state of spin-1/2 models containing chiral three-spin interactions that drive a uniform scalar spin chirality [16][17][18][19][20][21]. In spin-1 models, the same interactions give rise to a non-Abelian CSL analogous to the Moore-Read state [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Chiral spin liquids (CSLs) [11][12][13] have been extensively studied since Kalmeyer and Laughlin proposed a spin wave function analogous to fractional quantum Hall states [14,15]. The Kalmeyer-Laughlin CSL can be stabilized as the ground state of spin-1/2 models containing chiral three-spin interactions that drive a uniform scalar spin chirality [16][17][18][19][20][21]. In spin-1 models, the same interactions give rise to a non-Abelian CSL analogous to the Moore-Read state [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…from which we conclude that lim λ→0 κ 3 (λ) = 0 (18) implying that the vector-spin-chirality long range order is excluded.…”
Section: Heisenberg Chain and Vector-spin-chirality Ordermentioning
confidence: 62%
“…Very recently, studying the so-called Y junctions made of spin-1/2 Heisenberg chains, it has been shown that a network of these junctions, with uniform coupling constants, may realize chiral spin liquid phases [16,17]. Remarkably, a controlled analytical investigation of these chiral spin liquid states may be realized by means of a honeycomb lattice of Heisenberg spin-1/2 chains, with three-spin Y junction interactions [18]. Finally, by means a non-abelian symmetry realization of the DM RG technique the behaviour of some chiral correlation functions in isotropic frustrated spin chains with s = 1 and s = 1/2 in an external magnetic field has been studied; it is found that the order does exist in the high field condition, both for s = 1 and s = 1/2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous suggestions for realizations of spin liquid phases include interaction of three nearest-neighbour spins that breaks time reversal symmetry in the form of a mixed product of three spins (see Refs. [56][57][58][59] and references therein). Instead of having such interactions, our model contains more attainable current-current interactions, and breaks time reversal symmetry by the use of IQH islands.…”
Section: Discussionmentioning
confidence: 99%